2016
DOI: 10.1017/rdc.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 14C Analysis of Dissolved Organic Carbon in Non-Saline Waters

Abstract: 23The 14 C content of dissolved organic carbon (DOC) in rivers, lakes, and other non-saline waters 24 can provide valuable information on carbon cycling dynamics in the environment. DOC is 25 typically prepared for 14 C analysis by accelerator mass spectrometry (AMS) either by UV 26 oxidation or by freeze-drying and sealed tube combustion. We present here a new method for the 27 rapid analysis of 14 C of DOC using wet chemical oxidation (WCO) and automated headspace 28 sampling of CO2. The approach is an adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Further precautionary steps, such as UV oxidation of water immediately prior to use, are therefore recommended to minimize this potential source of contamination. Lang et al (2016) showed that the contamination from WCO can be as low as 0.68 µg C which is at least consistent with blank values reported for the other combustion techniques and would result in a total contamination of 1.33 µg C if attained in this study. Additionally, this study used the same experimental setup as Lang et al (2013) of 5 mL solvent (sample and oxidant in water) in 12 mL Exetainer vials yet, this could possibly be reduced to 3 mL solvent.…”
Section: Allocation Of Constant Contamination To Subproceduressupporting
confidence: 91%
See 4 more Smart Citations
“…Further precautionary steps, such as UV oxidation of water immediately prior to use, are therefore recommended to minimize this potential source of contamination. Lang et al (2016) showed that the contamination from WCO can be as low as 0.68 µg C which is at least consistent with blank values reported for the other combustion techniques and would result in a total contamination of 1.33 µg C if attained in this study. Additionally, this study used the same experimental setup as Lang et al (2013) of 5 mL solvent (sample and oxidant in water) in 12 mL Exetainer vials yet, this could possibly be reduced to 3 mL solvent.…”
Section: Allocation Of Constant Contamination To Subproceduressupporting
confidence: 91%
“…The screwcapped vials were then purged with ultra high purity helium at 100 mL min -1 for 8 min. Oxidation of the samples is achieved by placing the vials in a heating block at 95°C for 1 hr (Lang et al 2016). Measurement: Gas Ion Source AMS Gaseous samples were measured with a MIni CArbon DAting System (MICADAS, Ionplus, Switzerland) AMS fitted via a carbonate handling system modified with a needle for sparging solutions Wacker et al 2013).…”
Section: Wet Chemical Oxidationmentioning
confidence: 99%
See 3 more Smart Citations